2016
DOI: 10.1080/00015458.2016.1255005
|View full text |Cite
|
Sign up to set email alerts
|

A one-step conversion from gastric banding to laparoscopic Roux-en-Y gastric bypass is as safe as a two-step conversion: A comparative analysis of 885 patients

Abstract: Converting a LAGB to RYGB can be performed with a very low morbidity and zero-mortality in a high-volume revisional bariatric center. With increasing experience and full standardization of the conversion, the vast majority of operations can be performed as a single-stage procedure. Only a migrated band remains a formal contraindication for a one-step approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…The present study entailed a major complication rate of 15.2%, which is comparable to the literature, where major complication rates are reported from 0 to 23% [5,8,9,11,12,14] in R-LRYGB. Our complication rate is even comparable to that for primary LRGBY: a review of 3464 cases with primary LRYGB reported a major complication rate of 11.7% [25].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The present study entailed a major complication rate of 15.2%, which is comparable to the literature, where major complication rates are reported from 0 to 23% [5,8,9,11,12,14] in R-LRYGB. Our complication rate is even comparable to that for primary LRGBY: a review of 3464 cases with primary LRYGB reported a major complication rate of 11.7% [25].…”
Section: Discussionsupporting
confidence: 85%
“…The same applies for our longer LOS as compared to that in the literature [11,14,15,24], which can also be explained by the Austrian health economics system not having the same pressure to discharge patients early, as compared to other countries.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations